2016
DOI: 10.15197/ejgm.01476
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Atherogenic Risk in Sleep Apnea Patients

Abstract: Objective: Some studies have shown the atherogenic dyslipidemia as being sometimes independent of the obesity; however, with a close relation to the obstructive sleep apnea (OSA). The aim of this study was to investigate a relationship between parameters defining the quality of sleep and the standard lipid profile despite the obesity. Methods: The data of 211 patients with suspected OSA were analyzed prospectively. The following tests were performed: polysomnography, morphometric assessment and serum lipid lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…After excluding patients in the study by Bikov et al [ 28 ], because patients were similar to another study published in 2022 [ 7 ], 14,943 cases (OSA and non-OSA) were evaluated in included studies. Eight studies evaluated AIP [ 7 , 8 , 28 , 29 , 31 33 , 35 ], while five studies evaluated LAP [ 5 , 7 , 27 , 34 , 36 ], and five studies evaluated VAI [ 7 , 20 , 30 , 34 , 36 ]. Table 1 summarizes the details of the studies along with their main findings.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding patients in the study by Bikov et al [ 28 ], because patients were similar to another study published in 2022 [ 7 ], 14,943 cases (OSA and non-OSA) were evaluated in included studies. Eight studies evaluated AIP [ 7 , 8 , 28 , 29 , 31 33 , 35 ], while five studies evaluated LAP [ 5 , 7 , 27 , 34 , 36 ], and five studies evaluated VAI [ 7 , 20 , 30 , 34 , 36 ]. Table 1 summarizes the details of the studies along with their main findings.…”
Section: Resultsmentioning
confidence: 99%
“…They found that AIP was higher in OSA and was related to AHI [ 21 ]. Wysocki et al investigated 211 patients with OSA and found a significant relationship between AHI and AIP; however, the authors did not recruit any controls [ 22 ]. Finally, Silva et al compared patients with mild OSA to controls and found increased TGs/HDL-C ratio in the OSA group.…”
Section: Discussionmentioning
confidence: 99%
“…Lower TC levels in the OSA group were, therefore, likely due to an increased usage of statins in these patients. In the previous studies, patients on statins were either included [ 19 , 22 ], excluded [ 21 ], or the results were adjusted for statin usage [ 18 , 23 ]. Nevertheless, excluding patients on statins did not change our conclusions on AIP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations